Development and In Vivo Assessment of an Injectable Cross-Linked Cartilage Acellular Matrix-PEG Hydrogel Scaffold Derived from Porcine Cartilage for Tissue Engineering - Ju, Hyeon Jin; Ji, Yun Bae; Kim, Shina; Yun, Hee Woong; Kim, Jae Ho; Min, Byoung Hyun; Kim, Moon Suk (Macromolecular Bioscience, 2023)
The cartilage acellular matrix (CAM) derived from porcine cartilage, which does not induce significant inflammation and provides an environment conducive for cell growth and differentiation, is a promising biomaterial candidate for scaffold fabrication. However, the CAM has a short period in vivo, and the in vivo maintenance is not controlled. Therefore, this study is aimed at developing an injectable hydrogel scaffold using a CAM. The CAM is cross-linked with a biocompatible polyethylene glycol (PEG) cross-linker to replace typically used glutaraldehyde (GA) cross-linker. The cross-linking degree of cross-linked CAM by PEG cross-linker (Cx-CAM-PEG) according to the ratios of the CAM and PEG cross-linker is confirmed by contact angle and heat capacities measured by differential scanning calorimetry. The injectable Cx-CAM-PEG suspension exhibits controllable rheological properties and injectability. Additionally, injectable Cx-CAM-PEG suspensions with no free aldehyde group are formed in the in vivo hydrogel scaffold almost simultaneously with injection. In vivo maintenance of Cx-CAM-PEG is realized by the cross-linking ratio. The in vivo formed Cx-CAM-PEG hydrogel scaffold exhibits certain host–cell infiltration and negligible inflammation within and near the transplanted Cx-CAM-PEG hydrogel scaffold. These results suggest that injectable Cx-CAM-PEG suspensions, which are safe and biocompatible in vivo, represent potential candidates for (pre-)clinical scaffolds.
Keywords: Acellular matrices; Cartilage acellular matrix; Crosslinker; Hydrogel scaffolds; In-vivo; Injectable hydrogel scaffold; Injectable hydrogels; Injectables; Polyethylene glycol cross-linker; Tissues engineerings; Animals; Biocompatible Materials; Cartilage; Hydrogels; Inflammation; Polyethylene Glycols; Suspensions; Swine; Tissue Engineering; Tissue Scaffolds; cartilage acellular matrix; injectable hydrogel scaffold; polyethylene glycol cross-linker